En Inde, dans les salles de cinéma, les spectateurs sont-ils acteurs ou simples spectateurs ? - Wendy Cutler (Conserveries Mémorielles)
The spectator’s role in general is often questioned, but in the case of Indian spectators, it takes a whole new turn. Indeed, in India, since the arrival of cinema, members of the audience do not content themselves with being simply spectators of the films projected. In that way, they distinguish themselves from their original role attributed by the epic poem, the Ramayana, in which they watched Sita’s sacrifice without reacting. Therefore, we can ask ourselves if we could qualify the audience as a “spectactor”, neologism used within the framework of Information and Communication Sciences. In order to deal with this question, we propose to study the drama’s audience and Aristotle’s notion of catharsis. In doing so, we will establish a parallel with the “contrat de feintise”2 that appears in the Nâtya-Shâstra (a treaty on drama), and we will see how this deal passed between the spectators and the play can be applied to the film audience in India. Moreover, in a more general analysis of the role of film audiences, we will explain how Indian spectators distinguish themselves from Western spectators, for example in their attitudes towards film projections. This will enable us to question the interactivity between the audience and the film projected.